Kejahatan Berbahasa Siber pada Meme di Media Sosial : Kajian Linguistik Forensik - Yuniar Andini Safitri; Mahsun Mahsun; Ahmad Sirulhaq (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
Technological developments have given birth to memes as a popular form of communication on social media. In addition to their entertainment function, memes often contain hate speech, insults, slander, and provocation that have the potential to violate the law and are classified as cybercrimes. This study aims to analyze the linguistic structure, meaning, and implied context in digital memes that have the potential to be criminal. The study uses a qualitative method with a forensic linguistic approach and critical discourse analysis. The research objects are memes circulating on social media in the period 2024-2025, selected based on indications of hate speech, defamation, or provocation according to the provisions of the ITE Law and the Criminal Code. The results show that memes often utilize linguistic ambiguity, irony, sarcasm, and metaphors to disguise the intent of insults or hatred that can trigger social conflict and legal consequences. Social cognitive analysis reveals the relationship between discourse structure, ideology, and power relations in digital society. In addition, syntactic-semantic-pragmatic analysis is able to reveal the spectrum of linguistic aggression in the digital space. This research provides a theoretical contribution to the development of forensic linguistics, as well as practical benefits for increasing digital literacy and legal awareness in the cyber era.